Pengembangan Perangkat Pembelajaran Berdasarkan Problem Based Learning terhadap Peningkatan Kemampuan Pemahaman Konsep Siswa - Wita Sinaga; Tuty Novelinda Purba; Folala Telaumbanua; Ruthmayasari Simanjuntak (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to develop learning tools in the form of lesson plans and worksheets based on Problem Based Learning mathematics on comparative material for seventh grade junior high school students oriented to the ability to understand concepts. The quality of the developed products is assessed based on aspects of validity, practicality, and effectiveness. The learning device development procedure refers to the 4-D development model, namely Define, Design, Develop, and Disseminate. Due to the limitations of the researcher, the research was carried out until the develop stage. The subjects of this study were students of class VII ASMP Negeri 2 Dolok Pardamean, totaling 34 people. The results of the research, namely: 1) the resulting learning tools, in the form of: lesson plans, student activity sheets and concept understanding tests have met the criteria; 2) the effectiveness of learning tools is concluded based on the percentage of students who understand the concept of at least moderate is 85.29% of the 34 students who take the test and the achievement of the ideal percentage of time for each category of student and teacher activity. In conclusion, the development of learning tools in the form of lesson plans and worksheets based on Problem Based Learning on comparative materials for grade VII junior high school students proved to be effective and able to improve students' conceptual understanding. Keywords: Ability to understand concepts, Learning tools, Problem Based Learning